Strategi Badan Pendapatan Pengelolaan Keuangan dan Aset Daerah dalam Pengelolaan Pajak Reklame Tehadap Pendapatan Pendapatan Asli Daerah di Kota Surakarta Jawa Tengah - Sururama, Rahmawati; Johannes, Ayu Widowati; Pratama, Andhika Yoga (JEKP (Jurnal Ekonomi dan Keuangan Publik), 2023)
Abstract Regional taxes are one source of Regional Original Income (PAD), one of which is Advertisement Tax which is collected by the district/city level government. The city of Surakarta is an autonomous region with city status under Central Java Province which regulates its own regional income. However, the realization of existing advertisement tax revenues is fluctuating if we look at 2016-2019, the realization of advertisement taxes always fluctuates and even in 2017, the realization of advertisement tax revenues was below the previously planned budget with a difference of 1,065,738,850.00 and only in 2018 -2019 experienced an increase from the target that had been set. Based on the problem description above, the aim of this research is to find out the strategy of the Revenue Agency for Regional Financial and Asset Management in Managing Advertisement Taxes on Original Regional Income in the City of Surakarta, Central Java Province. This research will use a qualitative descriptive method with an inductive approach. Data collection techniques using observation, documentation, interviews (Creswell, 2014).. Data analysis techniques using data reduction, data display/data presentation, drawing conclusions/verification.. From the analysis of research results it is known that from the Internal Environmental Analysis Aspect, especially from Human Resources indicators are still lacking in terms of quantity but in terms of quality they are adequate, from the Fund Sources aspect it is still inadequate in terms of equipment maintenance costs, from the Social Aspect it is found that there is still a lack of public awareness as taxpayers to pay taxes on time and also report the active status of the advertisement and there are still individuals who place advertisements illegally and do not comply with applicable regulations. Keywords: Management, Tax,